Effects of packaging and postharvest cooling on quality of table grapes (Vitis vinifera L.) - Du Plessis, S. F. (Stephanus Francois) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric)--Stellenbosch University, 2003.